2022
DOI: 10.3389/frsc.2022.952034
|View full text |Cite
|
Sign up to set email alerts
|

Redefining energy vulnerability, considering the future

Abstract: Within the EU, energy poverty is believed to affect at least 9.8% of households. Energy poverty can be broadly defined as a households' inability to meet its energy needs. This is a problem that affects all European countries, but narrow interpretations of data based on notions of material deprivation may lead to energy poverty being overlooked or not considered an issue by policymakers. The EU Energy Poverty Advisory Hub makes a number of essential points when it comes to the measurement, definition, and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Also, the number of older people in one household seems to correlate with a higher risk of EP [32]. In contrast, some scholars argued that by controlling more factors such as income and household size, increasing in age may even associate with a lower probability of energy vulnerability [2].…”
Section: Previous Findingsmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, the number of older people in one household seems to correlate with a higher risk of EP [32]. In contrast, some scholars argued that by controlling more factors such as income and household size, increasing in age may even associate with a lower probability of energy vulnerability [2].…”
Section: Previous Findingsmentioning
confidence: 95%
“…Another frequently used standard for EP detection is the direct comparison between the level of pre-defined domestic energy service and the actual level achieved, like whether households are capable of maintaining a comfortable temperature in their main living room [13]. Recent EP literature tends to apply a multiple-indicator approach instead of a singular one [2,3,12,14] as a previous study has suggested that it may lead to misinterpretation of the problem as well as cause vulnerable populations to be left out [13]. A considerable number of papers also chose to apply a multidimensional interpretation of the definition, where specific and more detailed energy needs such as cooking, lighting, laundry, education, and commuting are taken into account [15].…”
Section: Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation